Obesity: risk of venous thrombosis and the interaction with coagulation factor levels and oral contraceptive use - Abdollahi, Morteza; Cushman, Mary; Rosendaal, Frits R. (Thrombosis and Haemostasis, 2003)
Deep vein thrombosis (DVT) is a common disease with an annual incidence of about 1 in 1000. Many risk factors have already been studied, both genetic and acquired. It is unclear whether obesity affects thrombotic risk in unselected patients. Obesity is common, with a prevalence of 20-25% and may therefore have a considerable impact on the overall incidence of thrombosis. We evaluated the risk of thrombosis due to overweight and obesity using data from a large population based case-control study.Four hundred and fifty-four consecutive patients with a first episode of objectively diagnosed thrombosis from three Anticoagulation Clinics in the Netherlands were enrolled in a case-control study. Controls were matched on age and sex to patients and were introduced by the patients. All patients completed a standard questionnaire and interview, with weight and height measured under standard conditions. The associations of obesity with clotting factor levels were studied to investigate possible mechanisms.Obesity (BMI ≥30 kg/m2) increased the risk of thrombosis twofold (CI95: 1.5 to 3.4), adjusted for age and sex. Obese individuals had higher levels of factor VIII and factor IX, but not of fibrinogen. The effect on risk of obesity was not changed after adjustment for coagulation factors levels (fibrinogen, F VIII, F IX, D-dimer). The relative risk estimates were similar in different age groups and in both sexes, indicating a larger absolute effect in older age groups. Evaluation of the combined effect of obesity and oral contraceptive pills among women aged 15-45 revealed that oral contraceptives further increased the effect of obesity on the risk of thrombosis, leading to 10-fold increased risk amongst women with a BMI greater than 25 kg/m2 who used oral contraceptives.Obesity is a risk factor for deep vein thrombosis. Among women with a BMI greater than 25 kg/m2 the synergistic effect with oral contraceptives should be considered when prescribing these.
Keywords: Venous thrombosis; obesity; body mass index; oral contraceptives